PEREMPUAN DALAM POLITIK MEDIA - Jannah (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2014)
The image of women in history is a wrenching day. Women's history is a history of continuous oppression. How native women in the Netherlands Colonialism era are treated also suggests common view time on women. The Founder of Batavia, Jan Pieterszoon Coen writing ' of women is a prerequisite in the trade. If women are available in the markets of the Indian trade, will be yours ' such declared Coen to the Heren XVII. And then the letter marked the beginning of days of misery for native women. Present, the condition was not getting lost, instead of the more. The mass media obviously contribute very unusual about the image to the woman. Massa Media capture is dominated by very bad image of women as a bully, destroyer husband career and others. In the political that very masculine image more bad, women only placed the stage just as a sweetener. While many ordinary women with remarkable achievement less get a place in the mass media. This writing offered a recitation against women especially in indonesia. The way of us read would determine our attitude and behavior against women which in turn will encourage everyone to put the figure corresponding undue women. Reward them elsewhere in the public and private space.